Analisis Pengendalian Internal Pengelolaan Dana Bantuan Sosial Kelompok Usaha Bersama (KUBE) dalam Menunjang Pencapaian Sustainable Development Goals (SDGs): Studi Kasus pada Dinas Sosial Provinsi Jawa Barat - Sintya Maghdani Riyanto; Siti Kustinah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the internal control in managing social assistance funds of Kelompok Usaha Bersama (KUBE). The research focuses on the effectiveness of control mechanisms, accountability, and transparency in the distribution and utilization of funds. The research method used is descriptive qualitative, with data collected through interviews, observations, and documentation. The results indicate that the implemented internal control still faces several challenges, such as limited supervision, lack of managerial understanding regarding accountability standards, and weak administrative documentation. Nevertheless, improvement efforts have been made through enhanced coordination among administrators and guidance from relevant stakeholders. This study recommends strengthening the monitoring system, providing training for administrators on financial governance, and improving transparency to ensure that the management of KUBE social assistance funds becomes more effective, accountable, and sustainable.